Control of flexible wings for mini UAVs - Lai, Benedict Chen Kin (2016)
In recent years, the world has been moving towards unmanned surveillance mainly for military security. This is highly beneficial as it eliminates any risk to the human operator. One such tool for unmanned surveillance is the miniature Unmanned Aerial Vehicle (UAV). The mini-UAV not only takes away risks to the human operator, it is smaller, lighter and more cost effective than conventional UAVs and can survey a large area quickly. It also requires only one operator to launch and operate the mini-UAV. However, one problem that a typical mini-UAV faces is that it has a low flight altitude where the wind conditions tend to be unpredictable. Thus, this project studies the use of flexible wing on UAVs for their smoother flight characteristics, which are the direct effect of the adaptive washout effect. In addition, the flexibility of the wing enables the wing to be folded around the fuselage for easy storage and deployment. While the flexible wing is preferred over a conventional rigid fixed wing aircraft, it faces the issue of ineffective roll control authority due to the absence of ailerons. This report discusses the novel solution of using tendon-sheath wing-warping mechanism as a substitute to ailerons. By warping the wing along its chord length, one can change the wing’s camber to manipulate lift generation. When only one side of the wing is warped, the difference in lift forces from both sides of the wing creates a rolling moment, exactly like ailerons. This report focuses on the control of the tendon-sheath wing-warping mechanism in particular.